A case of a patient with Takayasu arteritis treated with left subclavian artery stent implantation. Issue 4 (October 2015) - Choi, Young Kyun; Jung, Young Ok; Kim, Han Myun; Kang, Min-Kyung
Abstract Takayasu arteritis is an uncommon chronic inflammatory arteritis affecting large vessels, predominantly the aorta and its main branches. This disease, primarily known to be frequent in Asia and Latin America region, occurs mainly in young people between the ages of 15 and 25 years, with a male to female ratio of 1:9. Here, we report a young Asian female patient with Takayasu arteritis affecting multiple arteries and treated with percutaneous transluminal angioplasty. <Learning objective: Takayasu arteritis (TA) is rare. Although several cases reported angioplasty in patients with TA, this particular case shows clear images of multiple involvement of TA, which was difficult to categorize. Furthermore, this case also shows 8 months of follow-up prognosis after percutaneous balloon angioplasty with stent. In conclusion, this particular case not only shows clear images of a rare case of TA, but also showed new treatment option with 8 months of follow-up.>